DNA Interaction with 57Co-Bleomycin - Kakinuma, J.; Orii, H. (Nuklearmedizin - NuclearMedicine, 1982)
Tumor-diagnostic 57Co-bleomycin is a mixture of two isomers: types I and II. Interaction between these and DNA was studied by fluorescence spectrometry and thermal denaturation. The fluorescence study indicated that cobalt chelation resulted in a remarkable increase in the apparent DNA-bleomycin association constant and a slight increase in bleomy-cin-DNA binding; a remarkable difference was observed between the two isomers. In the thermal denaturation study, the difference of DNA binding behavior was also observed. The tumor affinity of these isomers was slightly different, and type I isomer showed higher tumor affinity than type II. These results indicate that cobalt chelation to bleomycin enhances DNA-bleomycin binding and its DNA binding stability, and these mechanisms, although not fully understood, appear to underly the difference in tumor affinity of cobalt-bleomycin isomers.